Designing giant Hall response in layered topological semimetals - Grigorii Skorupskii; Fabio Orlandi; Iñigo Robredo; Milena Jovanovic; Rinsuke Yamada; Fatmagül Katmer; Maia G. Vergniory; Pascal Manuel; Max Hirschberger; Leslie M. Schoop (Nature Communications)
Abstract Noncoplanar magnets are excellent candidates for spintronics. However, such materials are difficult to find, and even more so to intentionally design. Here, we report a chemical design strategy that allows us to find a series of noncoplanar magnets—Ln3Sn7 (Ln = Dy, Tb)—by targeting layered materials that have decoupled magnetic sublattices with dissimilar single-ion anisotropies and combining those with a square-net topological semimetal sublattice. Ln3Sn7 shows high carrier mobilities upwards of 17,000 cm2 ⋅ V−1 ⋅ s−1, and hosts noncoplanar magnetic order. This results in a giant Hall response with an anomalous Hall angle of 0.17 and Hall conductivity of over 42,000 Ω −1 ⋅ cm−1—a value over an order of magnitude larger than the established benchmarks in Co3Sn2S2 and Fe thin films.